Helicobacter pylori plasticity region genes are associated with the gastroduodenal diseases manifestation in India. Issue 1 (December 2016) - Ganguly, Mou; Sarkar, Sagartirtha; Ghosh, Prachetash; Sarkar, Avijit; Alam, Jawed; Karmakar, Bipul; De, Ronita; Saha, Dhira; Mukhopadhyay, Asish
Abstract Background Almost allHelicobacter pylori infected person develop gastritis and severe gastritis is supposed to be the denominator of peptic ulcer diseases, which may lead to gastric cancer. However, it is still an enigma why few strains are associated with ulcer formation, while others are not related with any disease outcome. Although a number of putative virulence factors have been reported forH. pylori, there are contradictory results regarding their connotation with diseases. Recently, there has been a significant attention in strain-specific genes outside thecag pathogenicity island, especially genes within plasticity regions. Studies demonstrated that certain genes in this region may play important roles in the pathogenesis ofH. pylori -associated diseases. The aim of this study was to assess the role of selected genes (jhp0940, jhp0945, jhp0947 andjhp0949 ) in the plasticity region in relation to risk ofH. pylori -related diseases in Indian population. Methods A total of 113H. pylori strains isolated from duodenal ulcer (DU) (n = 61) and non-ulcer dyspepsia (NUD) subjects (n = 52) were screened by PCR and Dot-Blot to determine the presence of these genes. The comparative study of IL-8 production and apoptosis were also done by co-culturing the AGS cells withH. pylori strains of different genotype. Results PCR and Dot-Blot results indicated that the prevalence rates ofjhp0940, jhp0945, jhp0947 andjhp0949 in theH. pylori strains were 9.8, 47.5, 50.8, 40.9 % and 17.3, 28.8, 26.9, 19.2 % isolated from DU and NUD, respectively. IL-8 production and apoptotic cell death were significantly higher inH. pylori strains containingjhp0945, jhp0947 andjhp0949 than the strains lacking those genes. Results indicated that the prevalence ofjhp0945, jhp0947 andjhp0949 are associated with increased risk of severe diseases in India. Conclusion Our study showed that presence ofjhp0945, jhp0947 andjhp0949 were significantly associated with symptomatic expressions along with the increased virulence during in vitro study whereasjhp0940 seems to be negatively associated with the disease. These results suggest thatjhp0945, jhp0947 andjhp0949 could be useful prognostic markers for the development of duodenal ulcer in India.